PENGARUH PENGGUNAAN TEHNIK PENCATATAN MIND MAPPING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI POKOK SISTEM EKSRESI MANUSIA - Rizki Sevtyn Pratiwi; Tri Jalmo; Rini Rita T Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
Mastery of concepts that are not quite optimal by high school science students of class IX N 2 Metro affected by the lack of proper strategies in the learning process. Strategies that can facilitate student achievement and skill one is mind mapping. Using mind mapping aims to determine students' critical thinking skills. Experimental research design was pretest-posttest form is not equivalent to involve XI IPA1 as the experimental class and control class XI IPA2 as selected by purposive sampling technique. The research data in the form of qualitative data obtained from students 'learning activities are analyzed using an index of students' critical thinking skills and mind mapping products derived from each group discussions and quantitative data obtained from a pretest-posttest were analyzed using t-test. The results showed improvement in the experimental class students' mastery of concepts with an average gain of 64.73 N-higher than the average N-gain the control class is 47.52. The average increase in each indicator of cognitive mastery of concepts by students in the experimental class also higher at 41.27 while the control class is 31.55. Similarly, student learning activities, that the experimental class achieving increased higher activity than the control class. Aspects express opinions / ideas and discuss work on LKS is the highest activity obtained by the students. Based on the achievements that have been disclosed, it can be concluded that the mind mapping is effective in improving students' critical thinking skills. Keywords: Mind mapping, critical thinking, student learning activities, subject matter                   Excretion system.